Simultaneous determination of synthetic dyes Ponceau 4R (E124) and Sunset Yellow (E110) by fluorimetry in soft drinks; Modern Analytical Chemistry - Nikolaeva A. A. Alyona Andreevna; Bulycheva E. V. Elizaveta Vladimirovna; Korotkova E. I. Elena Ivanovna; Linert W. Wolfgang (2018, 2018)
Title screen